Analisis Kadar Air, Kadar Abu, Volatil Dan Fixed Carbon Pada Biochar Cangkang Sawit Dengan Variasi Suhu Pirolisis - Almira, Ulimaz; Sasmita, Aryo; Isnaini, Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Palm shell has the potential as a biochar raw material because it contains hemicellulose, cellulose and lignin. The purpose of this study is to study the influence of pyrolysis temperature on the characteristics of biochar produced in accordance with SNI 06-3730-1995. Palm shell biochar is pyrolysis with temperature variations of 500 oC and 600 oC for 1 hour and activated using NaOH. Biochar palm shell has met SNI 06-3730-1995 for water content and volatile levels, while ash levels and fixed carbon levels are not in accordance with the requirements.Keywords : Biochar, palm shell, moisture, ash, vollatile, fixed carbon